2021
DOI: 10.30699/ijp.2020.130944.2452
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic and Prognostic Roles of Combined Expression of Novel Biomarkers in Lung Adenocarcinoma (LUAD) and Lung Squamous Cell Carcinoma (LUSC); An Immunohistochemical Study

Abstract: Lung squamous cell carcinoma Scan to discover onlineBackground & Objective: Diagnosis and discrimination of lung adenocarcinoma (LUAD) from lung squamous cell carcinoma (LUSC) is critical to select the appropriate treatment regimen as recently targeted therapies require accurate subtyping of nonsmall-cell lung carcinoma (NSCLCs). There are currently several biomarkers that could be used for differentiation between LUAD and LUSC, but they have less sensitivity, specificity, and clinical applicability. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Proper identification and classification of the various subtypes of lung carcinoma are crucial to enhance diagnosis, treatment, and patient outcomes. In the domain of lung carcinoma, protein biomarkers have gained increasing importance for the classification of subtypes based on the expression of specific proteins in tumor cells [43,44]. As an indispensable component of numerous biological data analysis pipelines, feature selection methods present a powerful tool for identifying the most informative protein biomarkers [45].…”
Section: Discussionmentioning
confidence: 99%
“…Proper identification and classification of the various subtypes of lung carcinoma are crucial to enhance diagnosis, treatment, and patient outcomes. In the domain of lung carcinoma, protein biomarkers have gained increasing importance for the classification of subtypes based on the expression of specific proteins in tumor cells [43,44]. As an indispensable component of numerous biological data analysis pipelines, feature selection methods present a powerful tool for identifying the most informative protein biomarkers [45].…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Antigen retrieval was achieved with 10 mmol/l sodium citrate for 24 minutes. The primary antibody was incubated for 16 minutes using rabbit monoclonal antibodies versus primary antibodies against rabbit monoclonal (PYCR1, 1:2000; Proteintech, [14][15][16][17] ) anti-BANF1 antibody [18][19][20][21] (1:100) with mouse anti-STARD8 (1:1,000; [22][23][24][25] Abcam) overnight at 4°C. Tissues were fixed in formalin 10%, and an automated method was used.…”
Section: Methodsmentioning
confidence: 99%
“…The adipophilin expression was increased in some lung adenocarcinomas (15.5%, 51/328–90%, 27/30), and only focal positive or negative in lung SCC and normal lung specimens 43 44. The upregulated adipophilin expression in lung adenocarcinoma suggested that it may be a potential marker of lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 95%